تقنيات الذكاء الاصطناعي وتأثيراتها على فاعلية محتوى وخدمات مؤسسات المعلومات: دراسة استشرافية - أحمد، أحمد فرج; سالم، زينب محمد هشام (المؤسسة العربية لإدارة المعرفة, 2022)
شهدت مؤسسات المعلومات انطلاق الثورة الصناعية الرابعة والتي تستند إلى تقنيات وتطبيقات الذكاء الاصطناعي المبتكرة، حيث تتمز باختلاف جذري مقارنة بالتقنيات السابقة لها سواء في عمق تأثيرها، أو درجة تشابكها، وارتباطها بمختلف المجالات، وبالتالي فهي تمثل تقنيات قائمة على المعرفة والتكنولوجيا، والتي من نماذجها الروبوتات، وتقنية النانو، والحوسبة الكمية، والتقنية الحيوية، وإنترنت الأشياء، والبيانات الضخمة، والواقع المعزز، والطباعة الثلاثية الأبعاد، والمركبات الذاتية القيادة، وغيرها. وعملت الدراسة الحالية على إبراز ملامح تطور تقنيات الثورات الصناعية الأربع وصولا لتطبيقات الذكاء الاصطناعي، واستشراف المفاهيم والسمات والخصائص ذات الصلة بهذه التطبيقات. واستهدفت الدراسة إلقاء الضوء على الرؤى والآفاق المستقبلية للتوجهات الجارية لتطبيقات الذكاء الاصطناعي، وبيان تأثيراتها على فعالية إدارة المحتوى الرقمي وخدمات مؤسسات المعلومات، مع التركز على ملامح هذا التأثير في ضوء المهام الرئيسة التي تقع في بؤرة الرؤى الاستراتيجية لمؤسسات المعلومات؛ كما قامت الدراسة باستشراف سبل توظيف تقنيات الذكاء الاصطناعي في إدارة المحتوى الرقمي وتعزيز خدمات مؤسسات المعلومات من خلال استعرض نماذج تطبيقية للقطاعات والمحاور التي يمكن توظيفها فيها. Information institutions have recently witnessed the launch of the fourth industrial revolution, which based on the technologies, and applications of the innovated Artificial Intelligence characterized by a radical difference if compared to the precedent technologies in terms of the depth of their impact, the degree of their intertwining or their relationship with a variety of fields. Therefore, they regarded as technologies based on the knowledge and technology some of whose domains are robotics, Nanotechnology, Quantum Computing, Biotechnology, Internet of Things, Big Data, 3D Printing, and Autonomous Vehicles etc. The recent study intended to highlight the most prominent features of the evolution of the four industrial revolutions technologies until the advent of the AI applications, and to explore the concepts, features and characteristics connected to these applications. The recent study also aims to shed light on the potential views and perspectives of the current trends pertaining to the AI applications and to demonstrate their influence on the effectiveness of managing the digital content and the services rendered to the information institutions and to focus on the features of this influence in light of the main tasks which are of great strategic importance to the information institutions. In addition, the study has demonstrated the techniques to apply AI technologies in the management of the digital content and reinforcing the services rendered to the information institutions through displaying applied models of the sectors and departments in which AI technologies can be apply.
Keywords: إدارة المحتوى الرقمي -- التحول الرقمي -- خدمات المعلومات -- البيانات الضخمة -- الواقع المعزز